政府在促进环保产业发展中的责任和作用 = On the roles of government in developing environmental protection industry - 杨志明 Yang, Zhiming (2008)
Environmental Protection (EP) is one of the most promising industries today, which has been shortlisted by China's government as the focus of development. According to the tenth 5-year plan for EP, there will be an investment as much as 700 billion Yuan during these five years, which may create a huge commercial opportunity for EP industry. However, it remains a topic requiring further study on how to convert the potential market into reality and how to make EP a growth point for China' economy.